TI_GERICHTE 14.2012.53 vom 20. April 2012 , Reclamo contro la dichiarazione di fallimento. Pseudova/Nova. Solvibilitâ verosimile - TI Tribunale d'appello (2012)
Reclamo contro la dichiarazione di fallimento. Pseudova/Nova. Solvibilitâ verosimile